HUMANITARIAN AID OF THE CZECHOSLOVAK RED CROSS FOR SOVIET RUSSIA AND UKRAINE DURING THE FAMINE OF 1921-1923s - G. G. Tsidenkov (Vestnik MGIMO-Universiteta, 2019)
The article highlights and summarizes the main aspects of the work of the Czechoslovak Red Cross in Soviet Russia and Ukraine during the famine of 1921-1923s. Its sources are documents from the Russian archives, the National Archives of Sweden, first introduced into scientific circulation in Russia, as well as the memories of the participants in the events. The substantial assistance to the starving population was provided by the Nansen International Relief Committee. One of the organizations that belonged to this Committee was the Czechoslovakian Red Cross. The Czechoslovakian Red Cross united several charitable organizations under its authority and worked in the regions most affected by the famine: in Samara province and in Berdyansk and Melitopol districts on the territory of the Ukrainian SSR and the Autonomous Crimean SSR. The aid was provided not only in the form of sending humanitarian supplies to the starving areas, but also by sending their own expedition of the Czechoslovak Red Cross to work in disaster-affected areas. The article reveals the scope of the assistance and provides some details on the activities of the Czechoslovak Red Cross in Soviet Russia and Ukraine during this period. Special attention is paid to a part of the wellknown history of the evacuation of children from the starving provinces to Czechoslovakia, namely the little-studied aspect of their re-evacuation after the end of the famine disaster. The article contains references to the receipt of Czechoslovak humanitarian aid to the starving people from the other organizations and sources, such as Workers International Relief, donations from private and official persons, works of art in favor of the starving.